Genetics of human infertility - Vogt, Peter H.; Schmid, M. (Monographs in human genetics, 2017)
Genetic basis of male and female infertility / R. Mallepaly, P.R. Butler, A.S. Herati, D.J. Lamb -- Genetics of premature ovarian failure : new developments in etiology opportunity / Y. Qin, J.L. Simpson, Z.-J. Chen -- Genetics of Klinefelter syndrome : experimental exploration / J. Wistuba, C. Brand, M. Zitzmann, O.S. Damm -- Human Y chromosome and male infertility : forward and back from azoospermia factor chromatin structure to azoospermia factor gene function / P.H. Vogt, U. Bender, J. Zimmer, T. Strowitzki -- Genetics and pathophysiology of the cystic fibrosis transmembrane conductance regulator in male reproduction : new evidence of a direct effect on the male germline / A. Touré -- The genetics of androgen receptor signalling in male fertility / L. O'Hara, L.B. Smith -- The genetics of postmeiotic male germ cell differentiation from round spermatids to mature sperm / T. Lehtiniemi, N. Kotaja -- The epigenetics of sperm chromatin / M.B. Shamsi, L. Simon, D.T. Carrell -- Characteristic features of male germline development in primates / R. Behr -- Genetic and epigenetic mouse models of human male infertility / M. Godmann, S. Zemter, C. Kosan -- In vitro spermatogenesis and its potential clinical implication for patients / J.-B. Stukenborg, K. Jahnukainen
Keywords: Aufsatzsammlung; Molekulargenetik; Genmutation; Sterilität